Introduzione - Conforti, Claudia; Belli, Gianluca; D’Amelio, Maria Grazia; Funis, Francesca (Opus Incertum, 2018)
Wooden coffered ceilings attest to the recovery of antiquity and the search for luxury in Renaissance architecture, first in Florence, then in Rome. They appear in 15th century Italian architecture with their formal and constructive perfection: carved, sculpted, painted, enriched with xylographies and plasters, in soft wood or in papier-mâché. Coffered ceilings, clad with gold or in bright red and blue colours, are polymateric masterpieces, the result of the work of several artisans, of transverse technical knowledge and of different artistic styles. Their diffusion in Renaissance architecture is sudden and pervasive: in a few decades they characterize the new interiors of Florentine building, such as the church of San Lorenzo, the Magi Chapel and some other rooms in the palazzo Medici. Simultaneously, in Rome, coffered ceilings emulate and surpass their former glory, renewing the naves of ancient basilicas – San Marco and Santa Maria Maggiore – as well as the great halls of stately aristocratic and curial palaces. This monographic issue aims at documenting and analysing, through some case studies, the revival of wooden coffered ceilings in the 15th century and their successive fortune; the techniques and the artists who conceived and executed them; the types of wood species used; the literary and artistic sources providing descriptions and instructions concerning their construction.